2022
DOI: 10.3389/fgene.2022.818241
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Clinical Features of Heterotaxy in a Prenatal Cohort

Abstract: Objectives: Some genetic causes of heterotaxy have been identified in a small number of heterotaxy familial cases or animal models. However, knowledge on the genetic causes of heterotaxy in the fetal population remains scarce. Here, we aimed to investigate the clinical characteristics and genetic spectrum of a fetal cohort with heterotaxy.Methods: We retrospectively investigated all fetuses with a prenatal diagnosis of heterotaxy at a single center between October 2015 and November 2020. These cases were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Wang et al’s results demonstrate that heterotaxy frequently associated with CA (11.7%), especially CNVs. However, other scholars conducted a CNV-seq analysis on heterotaxy and found that the incidence of CA was 4.2% (3/72) [ 17 ]. In other studies, the incidence of CA was also mostly concentrated at 2% [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al’s results demonstrate that heterotaxy frequently associated with CA (11.7%), especially CNVs. However, other scholars conducted a CNV-seq analysis on heterotaxy and found that the incidence of CA was 4.2% (3/72) [ 17 ]. In other studies, the incidence of CA was also mostly concentrated at 2% [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] This left 21 studies included in the final metaanalysis (incorporating 1957 cases). [19][20][21][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Of the 21 studies in this paper, 8 were used in the previous analysis by Mone, et al 10 Table S1 outlines the study characteristics. Supplementary Figure S1 demonstrates the quality assessment.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The term isomerism refers to cases in which right-sided structures or left-sided structures are found on both sides of the body. Patients with right isomerism typically present with the most severe phenotypes on the HTX spectrum (Yi et al, 2022). These patients often have bilaterally trilobed lungs, and the absence of a spleen (asplenia) that leaves them at risk for infections (Loomba et al, 2016a;Buca et al, 2018).…”
Section: Heterotaxy Syndromementioning
confidence: 99%
“…These patients often have bilaterally trilobed lungs, and the absence of a spleen (asplenia) that leaves them at risk for infections (Loomba et al, 2016a;Buca et al, 2018). Characteristic cardiac defects include atrioventricular canal defects, a single functional ventricle (or large ventricular septal defect), pulmonary valve stenosis or atresia, anomalous pulmonary venous return, and transposition of the great arteries (Saba et al, 2022;Yi et al, 2022). On the other hand, individuals with left isomerism will often have bilaterally bilobed lungs and multiple spleens (polyspenia).…”
Section: Heterotaxy Syndromementioning
confidence: 99%